2006
DOI: 10.1038/sj.onc.1209895
|View full text |Cite
|
Sign up to set email alerts
|

A redox cycle within the cell cycle: ring in the old with the new

Abstract: In recent years, the intracellular oxidation-reduction (redox) state has gained increasing attention as a critical mediator of cell signaling, gene expression changes and proliferation. This review discusses the evidence for a redox cycle (i.e., fluctuation in the cellular redox state) regulating the cell cycle. The presence of redox-sensitive motifs (cysteine residues, metal co-factors in kinases and phosphatases) in several cell cycle regulatory proteins indicate periodic oscillations in intracellular redox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
202
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(224 citation statements)
references
References 91 publications
21
202
0
1
Order By: Relevance
“…Values not sharing a common letter are significantly different at p \ 0.05 by TukeyKramer multiple comparisons test the treatment with pterostilbene could significantly increase the intracellular ROS level of the cells as early as 2 h after treatment. The fluctuations in the intracellular redox state during cell cycle progression could represent a fundamental mechanism linking oxidative metabolic processes to cell cycle regulatory processes (Menon and Goswami 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Values not sharing a common letter are significantly different at p \ 0.05 by TukeyKramer multiple comparisons test the treatment with pterostilbene could significantly increase the intracellular ROS level of the cells as early as 2 h after treatment. The fluctuations in the intracellular redox state during cell cycle progression could represent a fundamental mechanism linking oxidative metabolic processes to cell cycle regulatory processes (Menon and Goswami 2007).…”
Section: Resultsmentioning
confidence: 99%
“…ROS were traditionally thought of as toxic byproducts in cells, which damaged cellular macromolecules and led cells to apoptosis (Shackelford et al, 1999). However, in recent years, several studies have shown that ROS can function as signaling molecules that regulate numerous cellular processes, including proliferation (Sundaresan et al, 1995;Behrend et al, 2003;Menon and Goswami, 2007;Bartosz, 2009). This dual function of ROS is based on differences in their concentrations, pulse duration and subcellular localization (Laurent et al, 2005;Bartosz, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This dual function of ROS is based on differences in their concentrations, pulse duration and subcellular localization (Laurent et al, 2005;Bartosz, 2009). High concentration of ROS in G1/S phase led to cell senescence or apoptosis and, on the contrary, low ROS facilitated cell cycle progression and activation of cell cycle regulators, such as, CDK4/6, cyclin D1, RB, p21 and E2F1 (Laurent et al, 2005;Menon and Goswami, 2007;Sarsour et al, 2009). The cell cycle regulation involved in the enhancement of proliferation seems to be mediated by the increase in phosphorylation and thiol-redox reaction induced by many mitochondrial proteins, such as MnSOD (Sakamaki et al, 2006;.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle progression in animals is considered to be driven by an intrinsic redox cycle consisting of reductive and oxidative phases (81)(82)(83)(84)(85). The binding of growth factors, such as epidermal growth factor (EGF) to their receptors (such as EGFR) is facilitated by ROS generation leading to oxidation and activation of signaling pathways that trigger cell proliferation (85).…”
Section: Gsh Is Required For the Cell Cycle In Rootsmentioning
confidence: 99%